Laboratory fundamentals of microbiology - Pommerville, Jeffrey C. (Burlington, MA : Jones & Bartlett Learning, 2022)
"This popular lab manual that for years has taught students the basics of working in a lab and how to safely handle microorganisms, has been completely redesigned and updated. All labs have been expanded and reorganized to fit neatly into new sections of the lab, such as "Fungi", "Viruses", or "Biotechnology", and are presented from easiest to most challenging. New introductions for each section provide the appropriate context for the labs and connects the lab concepts to the core text, Fundamentals of Microbiology, Twelfth Edition. The most exciting update are the NEW videos available with the Lab Manual that teach common lab skills that tie to the labs in the manual. Students will clearly see how to work safely in the lab setting, how to use operating equipment, how to swab cultures, and many more lab skills. New photos and micrograph examples and new exercises and assessments only further enhance the twelfth edition of Laboratory Fundamentals on Microbiology, making it the easy choice for microbiology lab courses"--
Includes index.
Preceded by: Laboratory fundamentals of microbiology / Jeffrey C. Pommerville. Eleventh edition. [2018].
Keywords: Microbiology -- Laboratory manuals; Medical microbiology -- Laboratory manuals